Characterization of the complete mitochondrial genome and phylogenetic relationship of Caranx tille (Perciformes: Carangidae). (1st November 2016) - Ma, Hongyu; Ma, Chunyan; Zhang, Heng; Zhang, Xun; Feng, Chunlei; Zhang, Yu; Wang, Wei; Chen, Wei; Ma, Lingbo
Abstract: In the present study, we determined the complete mitochondrial genome sequence of Caranx tille by using Illumina and Sanger sequencing technology that was 16 593 bp in size. This mitochondrial genome was made up of 13 protein-coding genes, 22 transfer RNA genes, 2 ribosomal RNA genes, and a putative control region. Of these 37 genes, 28 were encoded by heavy strand, while nine were encoded by light strand. Three types of start codons and four kinds of stop codons were separately detected in 13 protein-coding genes. The overall base composition of this genome was 28.95% for A, 15.84% for G, 26.26% for T, and 28.95% for C, with a slight higher A + T content of 55.21%. From the phylogenetic tree constructed based on 13 concatenated protein-coding genes, we can see that C. tille, C. melampygus and C. ignobilis grouped together and formed a single cluster. In addition, C. tille was genetically closest to C. melampygus . This work should facilitate the studies on molecular evolution and population genetic structure for fishes under family Carangidae.